Metodologías para la reinserción inclusiva de jóvenes y adultos - Bajaña Quintana, Elida Yesenia (2021)
The lack of support from the teacher, who has not experienced being an educational facilitator for young people and adults in inclusive education, is shocking, since teachers are unaware of andragogic methodology, since most are teachers of initial, middle and secondary level, and They have only experienced a traditional didactics, that is why the objective was to determine the andragogical methodology for the reintegration of young people and adults of the ABC Monseñor Leónidas Proaño program. Being the investigation with a mixed approach, descriptive type, field, applying appropriate methods and techniques for data collection……….